Virtual City: Neurocognitive rehabilitation of Acquired Brain Injury - Dores, Artemisa Rocha (2019)
Acquired Brain Injury (ABI) is one of the leading causes of individuals' reduced participation in various contexts of life, compromising autonomous functioning and performance in complex activities. Neurocognitive rehabilitation, carried out by transdisciplinary teams, is part of the intervention after the acute phase, aiming patients' maximum functionality and quality of life. Serious games and virtual reality begin to provide innovative solutions in this area. In this study, a prototype platform for the rehabilitation of executive functioning and other related cognitive functions is presented: the Virtual City. Part of a larger project, it consists of urban virtual environments that simulate real-life scenarios and activities. Tests will be performed to validate it as a tool for the rehabilitation of ABI.